5-Fluorouracil as an Adjunct in Glaucoma Filtration Surgery in Younger Age Group - Harris Muzammil Ansari, Norin Iftikhar Bano, Tariq Mehmood Qureshi Muhammad Tariq Khan (Pakistan Journal of Ophthalmology, 2011)
Purpose: To evaluate efficacy and complication of 5-Flourouracil (5-FU) as an adjunct in trabeculectomy in young age group. Material and Methods: 86 eyes of 62 patients were included in the study. There were 48 male patients (55.81%) and 38 female patients (44.18%). Age of patients were two year to fifteen year. Duration of study was four years with average follow up of two years. Study was conducted at LRBT Eye Hospital Lahore. Trabeculectomy was performed with conventional method. First subconjuctival injection of 5-FU (50mg/0.2ml) was given at the end of the procedure, second at the end of 1st week and the third at the end of 2nd week. Additional 1-2 injections of 5-FU were given in more resistant cases. Results: Target IOP was achieved in 83 (96.51%) of patients, 2 (2.32%) patients were given additional medication to achieve target IOP and 1 (1.16%) did not achieve target IOP. Visual acuity remained stable in 69 (80.23%) patients, improved in 13 (15.12%) patients, while it deteriorated in 4 (4.65%) patients due to late complications. Cup-to-disc ratio reversal was seen in 30% patients up to 14 years of age Choroidal detachment occurred in 8 (9.30%) patients and was successfully treated with cycloplegics and pressure patching. Choroidal drainage was done in only one patient. Thin bleb was seen in 4 (4.65%) patients. Blebitis occurred in 1 (1.16%) patient that led to endophthalmitis. 2 (2.32%) patients had retinal detachment. Redo-trabeculectomy was done in 3 (3.48%) cases.